Indenone derivatives as inhibitor of human DNA dealkylation repair enzyme AlkBH3. Issue 14 (7th August 2018) - Nigam, Richa; Babu, Kaki Raveendra; Ghosh, Topi; Kumari, Bhavini; Akula, Deepa; Rath, Subha Narayan; Das, Prolay; Anindya, Roy; Khan, Faiz Ahmed
Graphical abstract: Highlights: Several novel indenone analogues have been synthesized. The products were screened against human DNA repair enzyme AlkBH3 by in vitro assay. Kinetics, ITC, CD experiments suggested that 5c binds to the active site of AlkBH3. Compound 5c inhibited proliferation of lung cancer cell line A549. Abstract: The mammalian AlkB homologue-3 (AlkBH3) is a member of the dioxygenase family of enzymes that in humans is involved in DNA dealkylation repair. Because of its role in promoting tumor cell proliferation and metastasis of cancer, extensive efforts are being directed in developing selective inhibitors for AlkBH3. Here we report synthesis, screening and evaluation of panel of arylated indenone derivatives as new class of inhibitors of AlkBH3 DNA repair activity. An efficient synthesis of 2, 3-diaryl indenones from 2, 3-dibromo indenones was achieved via Suzuki-Miyaura cross-coupling. Using a robust quantitative assay, we have obtained an AlkBH3 inhibitor that display specific binding and competitive mode of inhibition against DNA substrate. Finally, we established that this compound could prevent the proliferation of lung cancer cell line and enhance sensitivity to DNA damaging alkylating agent.